Interpretasi Lingkungan Pengendapan Formasi Batuan Menggunakan Analisis Elektrofasies di Lokasi Tapak Puspiptek Serpong - Syaeful, Heri; Muhammad, Adi Gunawan (EKSPLORIUM, 2017)
The activity of subsurface material composing site foundation characterization is part of nuclear installation siting study. Characterization conducted by several methods, such as understanding the depositional environment of rock formations. As a segment of depositional environment interpretation method, facies model analysis based on electrofacies provides quicker information on depositional system of rock formation. Methodology applied is gamma ray log (log GR) interpretation using relative correlation between log shape variation and sedimentation facies. Based on the analysis, Bojongmanik Formation was deposited on marine-lagoonal environment with very low wave influence. Log GR that shows shape of funnel, serrated, and symmetry, indicate shoreface, lagoon, and tidal point bar facies. The direction of sedimentation, basin, and supply of Bojongmanik Formation interpreted relatively to the north. Serpong Formation deposited on meandering river system, and composed of point bar deposit, crevasse splay, and floodplain deposit. The result of analysis is expected to be guidance in further analysis related to the characterization of foundation materials.